RESOURCE GOVERNANCE IN INDONESIA: CHALLENGES OF MINING PERMITS AND LAND USE RIGHTS - Pertiwi, Putri Indah; Surya Putri, A Salsabila Ivana; Amanda, Dina; Nabillah Arrista, Jihan; Rachmadianti, Keiza (Universitas Syiah Kuala, 2024)
Indonesia is renowned for its abundant natural resources. In alignment with Article 33, Paragraph 3 of the 1945 Constitution, which asserts that the earth, water, and natural resources in Indonesia are under state control and should be utilized for the maximum benefit of the people, the Indonesian government is tasked with overseeing these resources to enhance the welfare of its citizens. Nonetheless, ongoing conflicts arise from overlapping legal frameworks between Mining Business Permits (IUP) and Business Use Rights (HGU). These conflicts may stem from various factors and lead to significant losses for multiple stakeholders.This article employs a doctrinal methodology through a literature review, examining relevant books, journals, news articles, and online media to investigate these issues. It aims to inform the Indonesian public by providing an overview of the challenges associated with the intersection of IUP and HGU, as well as the government's responsibilities and potential solutions. By fostering a deeper understanding of these complexities, particularly for those involved in the mining industry, this article also calls upon the government to enhance regulatory oversight to mitigate such overlaps.